Chemotherapy in Neonates and Infants Pharmacological Oncology for Children Under 1 Year Old - Penteado Schmidt, Carolina Witchmichen (Springer International Publishing, 2018)
This book provides a comprehensive overview of pediatric oncology, discussing drug therapy and treatment in children under the age of 1 year. It is the first volume to focus on chemotherapy in newborns and infants, especially the daily clinical practice and treatment protocols. Intended as a practical manual, it addresses all the major topics related to pediatric oncology in an accessible and easy-to-use format. It examines topics in pediatric oncology therapeutics, including drug metabolism, excretion, toxicity, drugs that can be used for each week or month of the patient's life, dose adjustment and treatment protocols. Chemotherapy in Neonates and Infants focuses on the safe treatment of children in the first year of life, and is aimed at pediatric oncology/hematology institutions, clinics and departments. It is particularly valuable for researchers, pediatric oncology physicians, pediatric and neonatology physicians, oncology pharmacists and the other healthcare professionals directly involved in the chemotherapy of neonates and infants.